#TITLE_ALTERNATIVE# - AMERUL FAOZI NIM : 18112042, AZIZ
Digital Signal Processing (DSP) is used in the latest radio devices. Radio demands a variety of requirements for data processing in the baseband. OFDM which utilizes Inverse Fast Fourier Transform (IFFT) will streamline the bandwidth of the overlapping sampling frequency, the process of changing parallel data from IFFT to serial becomes one of the problems, because this process cannot be directly summed using adder. By using vector Walsh-Hadamard mapping, the data can be serialized directly by adding it using adder. The complexity value of Inverse Discrete Fourier Transform which is worse than the IFFT value makes IFFT more preferable to do this signal processing. IFFT values that are more linearly, linear than IDFTs which are more quadratic tend, IFFT used to provide a shorter processing time value for fourier transforms. In this final project the author compares the processes used to perform signal processing such as IFFT and IDFT. The process is done by comparing the performance of both of them on a certain repetition value, the value of the processing time both are represented in a graph. Testing of jamming to test the resistance of IFFT and CDMA modulation. Testing is done using python. Some of the python libraries used are numpy and matplotlib. Numpy for processing numerical processing and matplotlib to provide graphic information.